The Desire for Workers' Participation: Conflicting Forces in the Workplace - Bar-Haim, Aviad (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
The desire to participate in managerial affairs on the workers' part among unskilled and semi-skilled workers in a food factory is hypothesized here to be contingent on two factors: rewards' satisfaction (RS) and ideology toward participation (OP).